Asynchronous fault location in transmission lines considering accurate variation of the ground-mode traveling wave velocity - Liang, R.; Yang, Z.; Peng, N.; Liu, C.; Zare, Firuz (M D P I AG, 2017)
This paper proposes a grounding fault location method in transmission lines based on time difference of arrival (TDOA) of ground-mode and aerial-mode traveling waves (TWs). The frequency-dependent characteristics of transmission lines cause different frequencies to have different attenuations and phase lags of different frequency components in traveling waves, which leads to the change of TWs velocities with different propagation distances. Due to these different propagation paths, the wave velocity variations of ground-mode should be considered as a main variable while the velocity of aerial-mode can be seen as a constant factor. A quadratic function that can illustrate the tendency of variation of ground-mode wave velocity is proposed by considering the relation between the wave velocity and fault distance. The least squares method is used to solve the quadratic function of different lines. Combining the quadratic formula and the incident TWs of each mode detected at both terminals of the line, a novel fault location method is proposed. First, according to the maximum and minimum ground-mode velocities, a fault scope can be acquired. Then, more accurate fault scopes and ground-mode velocities can be obtained by iteration computation. Finally, an accurate fault position is acquired when the fault scope is sufficiently small. PSCAD/EMTDC software is used to conduct fault simulations in order to verify the feasibility and accuracy of the method.